Pengaruh Kepemimpinan DAN Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Wijaya Karya (PERSERO)Tbk - Arfah, Muhammad (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to determine the influence of leadership and organizational culture on employee performance at PT. Wijaya Karya (Persero), Tbk. The types of data used in this research are qualitative and quantitative data. Sources of data used are primary data and secondary data. The data analysis method used is descriptive analysis. Multiple linear regression, correlation coefficient, coefficient of determination, t test and f test. the results of this study that simultaneously leadership and organizational culture have a positive and significant effect on PT. Wijaya Karya (Persero), Tbk.